Analisis Pengaruh Green Product dan Green Advertising terhadap Keterlibatan Konsumen dan Dampaknya pada Keputusan Pembelian Konsumen Laksmie Florist - Tinjung Desy Nursanti; Melisa Melisa (Bina Nusantara University, 2011)
Marketing-oriented concept of community not only relies on community needs, but also can bring prosperity through environmental responsibility around; in this case the product and the marketing are more environmentally friendly. Application of green products and green advertising might attract widespread public sympathy, and even requirements for operational permits, production and ease of obtaining bank credit facility or tax relief may be considered by the government that is now more incentive to campaign for the concept and implementation of policies and regulations of corporate social responsibility. The objectives of this study was to determine whether there is influence of green product and green advertising toward consumer involvement and also its impact on consumer purchasing decisions Laksmi florist company. A survey with analysis of individual consumer of Lakmi florist is conducted, while path analysis is used to determine the effect among variables. The results showed that green advertising as well as green product provide a positive and significant influence on consumer involvement that have an impact on consumer purchasing decisions of Laksmi Florist company.